When doing less adds up to more : companies that reduce and simpllify front-line employee workload find that they can better position employees to deliver a better customer experience - Ton, Zeynep (MIT Sloan Management Review, 2023)
Executives typically add customer offerings such as new features or products or initiate new pilots, processes, and tools to spur business growth -- without considering how such changes will affect customer-facing workers' workloads and ability to serve customers. Based on research and experience with companies like Sam's Club, Mercadona, and Quest Diagnostics, the author explains how subtracting existing processes and product options rather than adding more can improve employee's work, retention, and wages and improve customer experience.